Pulmonary arterial pressure: repeated measures and dynamics due to changes in altitude and age - Zimprich, Taylor R., author; Thomas, Milt, advisor; Speidel, Scott, committee member; Holt, Tim, committee member (Colorado State University. Libraries, 2022)
High Altitude Disease (HAD) in cattle is a consequence of pulmonary hypertension (PH) induced by hypoxia at elevations > 1,500 m. Pulmonary arterial pressure (PAP) is a phenotypic indicator of animal susceptibility to PH and HAD and is moderately heritable (h2 = 0.26 to 0.34). The goal of this thesis was to evaluate repeated measures of PAP and dynamics. This goal was achieved with two studies and three objectives: 1) to explore and estimate correlations between different ages and elevations, 2) to determine usefulness of yearling moderate altitude PAP in beef bulls that are transported to high elevation for short- and longer-term management, and 3) to determine usefulness of feedlot entry PAP to additional PAP measures as the cattle approach finishing and harvest. The objective of Study I (Chapter 3) was to determine significant variables and estimate correlation between PAP measurements at moderate altitude and high altitude at differing ages. This scenario often occurs in the Western U.S. beef industry. Data consisted of breed, sire, mean PAP (mPAP) measures at each collection date, elevation, and bull age, from 2017-2019 (n = 89) spring-born bulls at the Colorado State University (CSU) Agriculture Research, Development, and Education Center (ARDEC; 1,524 m). A potential 5 PAP measurements were collected from each bull: 1) Weaning PAP at ARDEC (1,525 m); 2) Yearling PAP at ARDEC; 3) PAP after acclimating for 28 days at Fort Lewis College (FLC; 2,470 m), Hesperus, CO; 4) before returning to ARDEC from FLC after 110 days at FLC; and 5) after re-acclimating for 57 days to the moderate elevation at ARDEC when the bulls were 557 ± 2.92 d (18 mo) of age. In model development, yearling PAP measurement, elevation, and age were determined to be important (P < 0.05) sources of variation. Also, PAP increased (P < 0.05) from moderate altitude to high altitude. In Study II (Chapter 4), yearling PAP in the model accounted for more variation in the prediction of the initial high-altitude PAP than it did in the prediction of the subsequent high altitude PAP measurements. Results of this study suggested that the yearling PAP measurement collected at 1,525 m was only a moderate predictor of a PAP measurement collected after 21 days at 2,470 m and these types of predictions weaken after ~ 90 days at high elevation. Overall, Study II (Chapter 4) suggested that as time increased (p < 0.05) between the mPAP measures the amount of variation accounted by the initial mPAP measure declined (p < 0.05). However, PAP has been considered to be the most accurate indicator of an individual's susceptibility to HAD if is measured at high altitude and near 18 months of age (Holt and Callen, 2007). This thesis suggested that yearling PAP measured at moderate elevations was a moderate and short-term indicator of future PAP performance in beef bulls when moving to high altitudes. Yearling PAP measurements are likely less indicative of PAP, the longer bulls reside at high elevation. It should be noted that high-altitude PAP observations will likely have higher correlations and be a stronger indicator to future high-altitude PAP measures. The altitude of the ARDEC facility (1,525 m) of CSU is moderate; therefore, questionable if it yields enough hypoxic stress to determine if a bull has PAP that will be acceptable or unacceptable for lifetime residence in a mountainous beef production system. Breed was not a significant variable in this thesis. This is likely due to limited numbers being evaluated in each breed. To further study breed influence, greater numbers of bulls being analyzed is necessitated. Therefore, this challenge warrants additional research when considering the diversity of beef operations in the Western US.
Keywords: bulls; pulmonary arterial pressure; Colorado; altitude